EMESIS DURING CHEMOTHERAPY: A REVIEW ON GRANISETRON, ITS EFFICACY AND DELIVERY SYSTEMS - Sharma, Vani; Arora, Saahil (International Journal of Current Pharmaceutical Research, 2015)
Nausea and vomiting are common problems occurs in disease, non-disease condition and after the chemotherapy, results from the activation of protective physiological mechanism in order to eliminate the toxin from the body. Principal four pathways that act on vomiting center to trigger nausea and vomiting are chemotherapy trigger zone (CTZ), cortex, peripheral pathway and the vestibular system. In emesis different treatment strategy are used in which Granisetron is a drug emerge as a drug of great potential to overcome chemotherapy induce nausea and vomiting. Current review aims to introduce emesis (CIE) during chemotherapy along with different novel therapeutic approaches and various clinical studies. In variety of studies to overcome the CIE novel approaches are of great importance.